Leadership and governance for occupational health and safety in the Philippines - Lacsamana, Guillano C. (2018)
Leadership and governance is an important element in the national occupational health and safety (OHS) system of any country. According to the International Labour Organization (ILO), and as supported by global studies, the four elements of leadership and governance include: (1) legislations for OHS; (2) lead agencies for the development ofOHS policies, programs, and services; (3) mechanisms for tripartite collaboration among the government, the management, and its workers; (4) mechanisms for the enforcement of OHS standards. This study aims to determine the presence of these elements in the Philippine OHS system, and to identify gaps as compared to the ILO standard. With the presence of an available database of legislations for OHS in the country, almost all elements of the leadership and governance system are supplied for, except for some rights of workers? representatives in the conduct of their roles and responsibilities for OHS. Despite this, there are still gaps in the functioning of each of these elements, which are mainly due to OHS not being a priority in the national agenda as well the lack of coordination among the lead agencies for OHS in the country and of the collaboration and coordination networks among these lead agencies can be a detrimental step in the improvement of leadership and governance for OHS in the Philippines.